Antioxidant CPA-type indole alkaloids produced from the deep-sea derived fungus Aspergillus sp. SCSIO 41024 - Wei-Hao Chen; Kun-Long Li; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Jun-Jian Wang; Yong-Hong Liu; Jun-Feng Wang (Natural Product Research, 2021)

The xyloglucan galactosylation modulates the cell wall stability of pollen tube - Qiqi Wei; Ying Yang; Hui Li; Zhiwen Liu; Rong Fu; Hanqian Feng; Chao Li (Planta, 2021)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Molecular cloning of myosin chaperone uncoordinate-45B (UNC-45B) and its heat stress response in the muscle of Pacific bluefin tuna Thunnus orientalis - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Uno Yamashita; Yan-Rong Jiang; Xiao-Mi Sun; Kazuya Shirota; Yasuhiko Shiina; Kiyoshi Osatomi (Fisheries Science, 2021)

Motor Circuit and Superior Temporal Sulcus Activities Linked to Individual Differences in Multisensory Speech Perception - Liyuan Li; Rong Li; Xinju Huang; Fei Shen; Hongyu Wang; Xuyang Wang; Chijun Deng; Chong Wang; Jiale Yang; Leiyao Zhang; Jiyi Li; Ting Zou; et al. (Brain Topography, 2021)

Spatial distribution and influencing factors of Surface Nibble Degree index in the severe gully erosion region of China’s Loess Plateau - Yi Zhou; Caiqin Yang; Fan Li; Rong Chen (Journal of Geographical Sciences, 2021)

Analysis on improvement effect of subgrade by dynamic compaction - Hui Qi; Chenjun Yang; Chao Hu; Yu Rong; Zhanyong Yao; Hongguang Jiang; Kai Yao; Luchuan Chen; Hui Li; Xianfei Teng (Arabian Journal of Geosciences, 2021)

Development and application of the Faba_bean_130K targeted next-generation sequencing SNP genotyping platform based on transcriptome sequencing - Chenyu Wang; Rong Liu; Yujiao Liu; Wanwei Hou; Xuejun Wang; Yamei Miao; Yuhua He; Yu Ma; Guan Li; Dong Wang; Yishan Ji; Hongyan Zhang; et al. (Theoretical and Applied Genetics, 2021)

Study on the Influence of Close Distance Construction of Urban Tunnel on the Existing Station - Yang Zheng; Ke Wu; Jie Sun; Rong Chen; Yameng Li; Shifeng Yang (Geotechnical and Geological Engineering, 2021)

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Recombinant L-HN Fusion Antigen Derived from the L and HN Domains of Botulinum Neurotoxin B Stimulates a Protective Antibody Response Against Active Neurotoxin - Zhen Li; Jian-Sheng Lu; Shan Liu; Rong Wang; Qing Xu; Yun-Zhou Yu; Zhi-Xin Yang (Neurotoxicity Research, 2021)

Exposure to antibiotics and mental disorders in children: a community-based cross-sectional study - Jingjing Zhang; Kaiyong Liu; Liang Sun; Linsheng Yang; Xinji Liu; Yitian Zhu; Rong Wei; Zhongxiu Jin; Li Wang; Ying Ma; Sufang Wang; Annuo Liu; et al. (Environmental Geochemistry and Health, 2021)

Oceanobacillus salinisoli sp. nov., a bacterium isolated from saline soil of Turpan city in Xinjiang province, north–west China - Wen-Yong Zhu; Li Yang; Zhou-Tian-Le Zhang; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Gang-Qiang Jiang; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

Syntheses and anticancer activities of novel glucosylated (−)-epigallocatechin-3-gallate derivatives linked via triazole rings - Bo-Ya Shi; Ze-Hao Wang; Ning Zhang; Yin-Rong Xie; Xiu-Li Sun; Hao-Nan Yang; Yi-Long Wu; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Medicinal Chemistry Research, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Isolation and identification of antimicrobial metabolites from sea anemone-derived fungus Emericella sp. SMA01 - Yang Yue; Huahua Yu; Rongfeng Li; Linfeng Hu; Song Liu; Rong’e Xing; Pengcheng Li (Journal of Oceanology and Limnology, 2021)

Quantitative Relationship Between Paddy Soil Properties and Cadmium Content in Tobacco leaves - Shuhui Duan; Jiashuo Yang; Zhicheng Zhou; Yansong Xiao; Sijun Li; Weiai Zeng; Huiyu Zeng; Xiangmin Rong (Bulletin of Environmental Contamination and Toxicology, 2021)

Haloechinothrix aidingensis sp. nov., an actinomycete isolated from salt lake in Xinjiang province, north-west China - Li Yang; Ya-Rong Kou; Tong-Wei Guan; Min Yin; Bing-Bing Liu; Yong-Jiang Shi; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Effect of bFGF on fibroblasts derived from the golden snub-nosed monkey - Xin Liu; Hao Wei; Jing Yang; Jingjing Li; Pei Zhang; Yuli Li; Rong Hou; Jinlian Hua; Xingrong Yan; Baoguo Li (Primates, 2021)

Identification of genetic variants in m6A modification genes associated with pancreatic cancer risk in the Chinese population - Pingting Ying; Yao Li; Nan Yang; Xiaoyang Wang; Haoxue Wang; Heng He; Bin Li; Xiating Peng; Danyi Zou; Ying Zhu; Rong Zhong; Xiaoping Miao; et al. (Archives of Toxicology, 2021)

Knockdown of Arginyl-tRNA Synthetase Attenuates Ischemia-Induced Cerebral Cortex Injury in Rats After Middle Cerebral Artery Occlusion - Yang Liu; Xue-Bin Hu; Li-Zhi Zhang; Zi Wang; Rong Fu (Translational Stroke Research, 2021)
Some researchers have previously shown that RNAi knockdown of arginyl-tRNA synthetase (ArgRS) before or after a hypoxic injury can rescue animals from death, based on the model organism, C. elegans . However, there has been no study on the application of arginyl-tRNA synthetase knockdown in treating mammalian ischemic stroke, and its potential mechanism and effect on ischemic brain damage are still unknown. Here, we focused on the Rars gene, which encodes an arginyl-tRNA synthetase, and examined the effects of Rars knockdown in a permanent middle cerebral artery occlusion model in rats. To achieve this aim, adult male Sprague-Dawley (SD) rats were given right cerebral cortex injections of short hairpin RNA (shRNA) adenovirus (AV) particles to knock down arginyl-tRNA synthetase, and a non-targeting control (NTC) vector or phosphate-buffered solution served as the controls. After 4 days, the rats were exposed to permanent middle cerebral artery occlusion (pMCAO). Then, the right cerebral cortex level of arginyl-tRNA synthetase was examined, and the effects of the Rars knockdown were evaluated by differences in infarction volume, oxidative stress, blood-brain barrier, mitochondrial function, and glucose metabolism at 1 day and 3 days after MCAO. The injection of shRNA adenovirus particles successfully suppressed the expression of arginyl-tRNA synthetase in the cerebral cortex. We observed an improvement in oxidative stress, mitochondrial function, and glucose utilization and a reduction in brain edema compared with the non-targeting control rats with suppressed expression of arginyl-tRNA synthetase mRNA in the ipsilateral ischemic cortex of the brain. Our findings indicate that knockdown of arginyl-tRNA synthetase in the cerebral cortex exerted neuroprotective effects, which were achieved not only by the improvement of oxidative stress and glucose utilization but also by the maintenance of mitochondrial morphological integrity and the preservation of mitochondrial function. Knockdown of ArgRS administration could be a promising approach to protect ischemic stroke.

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Paeonol ameliorates CFA-induced inflammatory pain by inhibiting HMGB1/TLR4/NF-κB p65 pathway - Chen Qiu; Liu-Di Yang; Wen Yu; Dan-Dan Tian; Mei-Rong Gao; Wen-Ju Wang; Xu-Bo Li; Yu-Mei Wu; Min Wang (Metabolic Brain Disease, 2021)

Relationship Between Body Composition and Balance Performance in Older Adults with Hyperkyphosis - Phunsuk Kantha; Shiow-Chwen Tsai; Chien-Wen Hou; Rong-Sen Yang; Pei-Yu Su; Wei-Li Hsu (Journal of Medical and Biological Engineering, 2021)

Paenibacillus turpanensis sp. nov., isolated from a salt lake of Turpan city in Xinjiang province, north-west China - Li Yang; Hua-Wei Huang; Yun Wang; Ya-Rong Kou; Min Yin; Yu Li; Xue-Qian Wang; Gui-Fang Zhao; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Climate‐induced nonlinearity in pelagic communities and non‐stationary relationships with physical drivers in the Kuroshio ecosystem - Shuyang Ma; Yongjun Tian; Caihong Fu; Haiqing Yu; Jianchao Li; Yang Liu; Jiahua Cheng; Rong Wan; Yoshiro Watanabe (Fish and Fisheries, 2021)
Climate‐induced nonlinearity in biological variability and non‐stationary relationships with physical drivers are crucial to understand responses of marine organisms to climate variability. These phenomena have raised concerns in the northeastern North Pacific, but are out of the spotlight in the northwestern North Pacific in spite of potential implications for this productive system under increased climate variability. Pelagic communities in the Kuroshio ecosystem have both ecological and economic importance. However, patterns of climate‐induced nonlinearity in pelagic communities are not well understood, and existence of non‐stationarity in their relationships with physical drivers remains obscure. Here, we compile large numbers of climatic, oceanic and biological long‐term time‐series data and employ diverse statistical techniques to reveal such climate‐induced nonlinearity and non‐stationarity. Results show that pelagic communities in the Tsushima and Pacific areas (major areas in the Kuroshio ecosystem) had regime shifts in the late 1990s and late 1980s, respectively. Winter sea surface temperatures in the Kuroshio Current path and in the eastern part of East China Sea, which are respectively affected by the Kuroshio Current and Siberian High, correlate with dominant variability patterns in their pelagic communities. Furthermore, non‐stationarity was identified with threshold years in the 1990s in the Tsushima area and in the 1980s in the Pacific area as a possible result of the declined variances in the Siberian High and Aleutian Low, respectively. Our findings provide insights on spatial differentiation of climate‐induced nonlinearity and non‐stationarity, which are valuable for the management of pelagic communities in the northwestern North Pacific under changing climatic conditions.